Narración de experiencias espirituales para una toma de conciencia de la propia vida - Carlos Alberto Rosas-Jiménez (Franciscanum, 2019)
The human person is an open book which should first be read by oneself in order to later be read by others. Throughout history we have seen many spoken and written narratives in different parts of the world, that along with having a historical value contribute to self-knowledge looking up ones life reflected in that who narrates its own life; within many others, we could point out the narratives of spiritual experiences, such as the Confessions of St. Augustine. This kind of narrative work helps to come to the surface certain elements of oneself life that have been accumulated in the unconscious. For this reason, in the present we put emphasis on the value of the narrative work and in particular of spiritual experiences which we propose that helps to be aware of one’s own reality. We present the results of some online interviews from a religious movement which helps to clarify the influence of spiritual narratives in the awareness of one’s own life and a closer approach to God.